(untitled) - Dr. Shukriya Qadar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Women are thought to be symbols of sacrifice and devotion in Pashtun society, with the expectations of unquestioned obedience. They are seen as the living essence of their family and are either protected or sacrificed for the honor of the family. They do not have the opportunity to live their own lives independently. They constantly bear the burden of sacrifice and the hopes associated with it. They endure every hardship with patience. They do not wish to ignite the fire through protest and rebellion, which would lead to centuries of bloodshed. They divert the path of storms with their delicate bodies and continue to flow like sweet and clear springs of peace, with the aim of maintaining the balance of this society.